Sovereign Risk and Deposit Dynamics : Evidence from Europe - Grigorian, David (IMF Working Papers; Working Paper, 2016)
The unprecedented expansion of sovereign balance sheets since the global financial crisis has given a new meaning to the term sovereign risk. Developments in Europe since early 2010 presented new challenges for the functioning of private banks in an environment of heightened sovereign risk. This paper uses an innovative way of measuring the perception of sovereign risk and its impact on deposit dynamics during 2006-11. Using an extension of a common market discipline framework, it shows that exposure to sovereign risk may have limited the ability of banks in Europe to attract deposits. The results are robust to inclusion of conventional measures of bank performance and the sector-wide holdings of foreign sovereign debt.